Digital sequencing is improved by using structured unique molecular identifiers - Peter Micallef; Manuel Luna Santamaría; Mandy Escobar; Daniel Andersson; Tobias Österlund; Pia Mouhanna; Stefan Filges; Gustav Johansson; Henrik Fagman; Christoffer Vannas; Anders Ståhlberg (Genome Biology)
Abstract Digital sequencing uses unique molecular identifiers (UMIs) to correct for polymerase induced errors and amplification biases. Here, we design 19 different structured UMIs to minimize the capacity of primers to form non-specific PCR products during library construction using SiMSen-Seq, a PCR-based digital sequencing approach with flexible multiplexing capabilities suitable for tumor-informed mutation analysis. All structured UMI designs demonstrate enhanced assay performance compared with an unstructured reference UMI. The best performing structured UMI design shows significant improvements in all tested aspects of assay and sequencing performance with the ability to reliable detect low variant allele frequencies.